The Influence of Banking Understanding, Communication and Intensity of Assignment on Banking Accounting Learning Outcomes - Priandarnita, Kurnia; Listiadi, Agung (Economic Education Analysis Journal, 2022)
The purpose of this study was to analyze the effect of understanding banking, communication with banks, and the intensity of assignment on banking accounting learning outcomes partially and simultaneously in class XI PKM students at SMK Negeri 10 Surabaya. This type of research uses a quantitative research approach. The number of samples in this study were 81 students of XI PKM. The sampling technique used is proportional random sampling. Data collection techniques using tests and questionnaires. Classical assumption test and multiple linear regression analysis were used to analyze the collected data using the IBM SPSS Statistic 24 program. The results showed that banking understanding, communication with banks, and the intensity of assignment had a significant effect on banking accounting learning outcomes with an Fcount of 5, 112 and a significance of 0.003. Partially, understanding of banking affects the learning outcomes of banking accounting with a significance value of 0.011. Communication with the bank affects the learning outcomes of banking accounting with a significance value of 0.025. The intensity of the assignment affects the learning outcomes of banking accounting with a significance value of 0.047.